Composite anion exchange membrane and method of making
By coating a cross-linked anion exchange membrane with nano-inorganic materials to form an organic-inorganic composite membrane, the problems of mechanical properties and mass transfer resistance of anion exchange membranes in the process of hydrogen production by water electrolysis are solved. This results in anion exchange membranes with high ion conductivity, alkali resistance and long lifespan, thus improving the performance of water electrolysis single cells.
Patent Information
- Application Number
- CN202311129745.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2026-01-27
- Estimated Expiration
- 2043-09-04
AI Technical Summary
Existing anion exchange membranes suffer from low ion transport rates, high ohmic resistance, poor mechanical properties, insufficient dimensional stability and alkali resistance in water electrolysis for hydrogen production, resulting in short service life. Furthermore, the micro-gaps between the catalyst layer and the membrane layer lead to large mass transfer resistance, affecting electrolysis efficiency.
An inorganic coating is used to create a cross-linked anion exchange membrane. The polymer backbone is prepared by condensation reaction of biphenyl monomers and ketone monomers, and then undergoes nucleophilic substitution reaction with halogenated olefin monomers to form a cross-linked anion exchange membrane. Finally, nano-inorganic materials such as zirconium dioxide are coated on the membrane surface to form an organic-inorganic composite membrane. Click reaction and ultraviolet curing technology are used to improve the mechanical strength and hydrophilicity of the membrane.
It effectively inhibits membrane swelling, improves mechanical strength, maintains appropriate water absorption, promotes ion conduction, enhances the bonding force between the catalyst layer and the membrane layer, reduces mass transfer resistance, extends service life, and improves the performance of water electrolysis single cells.
Smart Images

Figure CN117046317B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a composite anion exchange membrane and its preparation method, and particularly to a highly hydrophilic organic-inorganic composite anion exchange membrane for hydrogen production by water electrolysis and its preparation method, belonging to the field of anion exchange membrane water electrolysis hydrogen production technology. Technical Background
[0002] Hydrogen energy is considered a renewable green secondary energy source that can be converted between chemical energy and electrical energy, and has advantages such as high energy density, high calorific value, and no pollution.
[0003] As a green energy conversion device for hydrogen production, anion exchange membrane electrolysis (AEMWE) offers advantages such as the ability to use platinum-free catalysts, faster oxygen evolution reaction kinetics, and a relatively mild reaction environment. Anion exchange membrane electrolysis not only retains the faster reaction kinetics and higher efficiency of proton exchange membrane electrolysis (PEMWE), but also possesses the advantage of alkaline water electrolysis (AWE) using no precious metal catalysts. Achieving efficient interconversion between electrical and chemical energy requires membrane electrode assemblies (MEAs) with low resistance, high stability, and long lifespan.
[0004] However, the anion exchange membrane (AEM), which is the core of the membrane electrode, still needs to improve the following properties: (1) increase the ion transport rate and reduce the ohmic resistance; (2) enhance the mechanical properties, dimensional stability and alkali resistance, and improve the service life of the anion exchange membrane; (3) reduce the interfacial mass transfer resistance between the electrolyte, the catalyst layer and the membrane (liquid-solid-solid), alleviate the micro gaps between the catalyst layer and the membrane layer, and improve the electrolysis efficiency.
[0005] Therefore, providing a composite anion exchange membrane and its preparation method that significantly shortens the membrane formation time, effectively inhibits membrane swelling, improves mechanical strength, maintains appropriate water absorption while reducing swelling to promote ion conduction, solves the problem of cross-linking reducing ion conductivity, extends service life, increases the bonding force between the catalyst layer and the membrane layer, alleviates the "micro-gap" between the membrane electrode, reduces mass transfer resistance, and enhances the performance of water electrolysis single cells has become a pressing technical challenge in this field. Summary of the Invention
[0006] One objective of this invention is to provide a composite anion exchange membrane that shortens the membrane formation time, effectively inhibits membrane swelling, improves mechanical strength, maintains appropriate water absorption while reducing swelling, promotes ion conduction, solves the problem of cross-linking reducing ion conductivity, extends service life, increases the bonding force between the catalyst layer and the membrane layer, alleviates the "micro-gap" between the membrane electrode assembly (MEA), reduces mass transfer resistance, and enhances the performance of a single water electrolysis cell.
[0007] To achieve the above-mentioned objectives of this invention, the following technical solution is adopted:
[0008] A composite anion exchange membrane is a composite membrane composed of an inorganic material and a cross-linked anion exchange membrane. The inorganic material is coated on the cross-linked anion exchange membrane, wherein the main chain structure of the cross-linked anion exchange membrane is as shown in general formula (I):
[0009]
[0010] Wherein: the polymer backbone is prepared by the condensation reaction of biphenyl monomers and ketone monomers (N-methylpiperidinone);
[0011] In the formula: n = 2 - 8;
[0012] x = 50, which is a percentage, and the corresponding anion is OH-. - I - or Br - ;
[0013] Ar represents biphenyl, terphenyl, and bibenzyl;
[0014] The inorganic material is zirconium dioxide, titanium dioxide, magnesium oxide, aluminum oxide, zinc oxide, iron tetroxide, ferric oxide, or copper oxide.
[0015] Preferably, the inorganic material is a nano-inorganic material.
[0016] Preferably, the nano-inorganic material is nano-zirconium dioxide, nano-titanium dioxide, nano-magnesium oxide, nano-aluminum oxide, nano-zinc oxide, nano-iron tetroxide, nano-ferric oxide, or nano-copper oxide.
[0017] Preferably, the organic-inorganic composite anion exchange membrane is a poly(biphenylpiperidine thiol) crosslinked composite anion exchange membrane (PBP-SH), a zirconium dioxide-poly(biphenylpiperidine thiol) crosslinked composite anion exchange membrane (PBP-SH-Zr1), a zirconium dioxide-poly(biphenylpiperidine thiol) crosslinked composite anion exchange membrane (PBP-SH-Zr2), or a zirconium dioxide-poly(biphenylpiperidine thiol) crosslinked composite anion exchange membrane (PBP-SH-Zr4).
[0018] Another object of the present invention is to provide a method for preparing the above-mentioned composite anion exchange membrane. The polymer backbone is prepared by the condensation reaction of biphenyl monomers and ketone monomers, followed by a nucleophilic substitution reaction with haloolefin monomers. A polymer with long olefin side chains is obtained, which is then subjected to a click reaction with a thiol monomer containing a thiol functional group to obtain a cross-linked anion exchange membrane. Finally, different amounts of zirconium dioxide ionomer are coated on the membrane surface to obtain an organic-inorganic composite anion exchange membrane.
[0019] To achieve the above-mentioned objectives of this invention, the following technical solution is adopted:
[0020] A method for preparing a composite anion exchange membrane, comprising the following steps:
[0021] (1) Dissolve biphenyl monomers in a solvent, add N-methylpiperidone in the reaction molar ratio, continue to add trifluoroacetic acid and trifluoromethanesulfonic acid, ice bath, stir, after the reaction is completed, pour the product into sodium hydroxide solution, stir, remove excess acid, wash with deionized water until neutral, dry for later use, and obtain polybiphenylpiperidin polymer.
[0022] (2) Dissolve the polybiphenylpiperidine polymer obtained in step (1) in a solvent, add 3-bromopropylene and potassium carbonate, heat and stir. After the reaction is complete, wash the product in a washing solvent, precipitate, and wash with deionized water to obtain polybiphenylpiperidine polyelectrolytes.
[0023] (3) Dissolve the polybiphenylpiperidine polyelectrolyte obtained in step (2) in a solvent, add iodomethane, stir at room temperature in the dark, and after the reaction is complete, wash the product in a washing solvent, precipitate, and wash with deionized water to obtain quaternized polybiphenylpiperidine polyelectrolyte.
[0024] (4) Dissolve the quaternized polybiphenylpiperidine polyelectrolyte prepared in step (3) in a solvent, add photoinitiator 2,2-dimethoxy-2-2-phenylethyl ketone and 1,8-octanedithiol, and carry out ultraviolet light reaction to obtain a homogeneous solution.
[0025] (5) Cast the homogenized liquid obtained in step (4) into a film and coat it with different contents of inorganic substances to obtain a coated film.
[0026] (6) Immerse the coated membrane obtained in step (5) in a sodium hydroxide or potassium hydroxide solution to obtain a hydroxide-type alkaline membrane.
[0027] Preferably, in step (1), the solvent is dichloromethane or trichloromethane; and the concentration of the sodium hydroxide solution is 3-5M.
[0028] Preferably, the biphenyl monomers mentioned in step (1) are biphenyl, terphenyl, or bibenzyl.
[0029] Preferably, in steps (2) and (4), the solvent is dimethyl sulfoxide, N-methylpyrrolidone, n-hexane, acetonitrile, cyclohexane, or N,N-dimethylformamide.
[0030] Preferably, in step (3), the solvent is dimethyl sulfoxide or N-methylpyrrolidone.
[0031] Preferably, in steps (2) and (3), the washing solvent is cyclohexane, acetonitrile, ethyl acetate or tert-butyl methyl ether.
[0032] Preferably, in step (1), the molar ratio of biphenyl monomers to N-methylpiperidone monomers is 1:1 to 1:1.5.
[0033] Preferably, in step (2), the molar ratio of polyaromatic piperidine polymer to 3-bromopropylene is 1:0.5; the reaction temperature is 80°C and the reaction time is 24-48 hours.
[0034] Preferably, in step (3), the molar ratio of polyarylene piperidine electrolyte to iodomethane is 1:1.3; and the reaction time is 24-72 hours.
[0035] Preferably, in step (4), the molar ratio of quaternized polybiphenylpiperidine polyelectrolyte to 2,2-dimethoxy-2-2-phenylethyl ketone is 1:0.1, and the molar ratio of quaternized polybiphenylpiperidine polyelectrolyte to 1,8-octanedithiol is 1:0.5; the ultraviolet light irradiation reaction time is 0.5-2h.
[0036] Preferably, in step (5), the inorganic material is a highly hydrophilic and alkali-resistant polar nano-inorganic material.
[0037] Preferably, in step (5), the polar nano-inorganic material is nano-zirconium dioxide, nano-titanium dioxide, nano-magnesium oxide, nano-aluminum oxide, nano-zinc oxide, nano-iron tetroxide, nano-iron tetroxide, or nano-copper oxide.
[0038] Preferably, in step (5), the amount of coated nano-inorganic material is 0 mg / cm³. 2 1mg / cm 2 2mg / cm 2 4mg / cm 2 .
[0039] Preferably, in step (6), the concentration of sodium hydroxide or potassium hydroxide solution is 0.1-3 mol / L, and the soaking time is 24-48 h.
[0040] Beneficial effects:
[0041] The inventors synthesized a series of zirconium dioxide-biphenylpiperidine thiol crosslinked composite membranes using a click (click chemistry, link chemistry, or quick-combination chemistry) crosslinking strategy and an organic-inorganic composite method. Biphenyl and N-methylpiperidine ketone, which have good alkali stability, were selected as the backbone and quaternary ammonium cation, respectively. Under ultraviolet light irradiation, 3-bromopropene, as a side chain, was reacted with 1,8-octanedithiol in a click reaction to synthesize a highly flexible network structure anion exchange membrane. Then, the surface of the membrane was coated with polar nano-zirconia with hydrophilicity and strong alkali resistance to form a "sandwich" structure composite anion exchange membrane.
[0042] The organic-inorganic composite anion exchange membrane obtained by this invention has the characteristics of high ion conductivity, excellent dimensional stability and alkali resistance. Secondly, coating with polar inorganic materials can increase the bonding force between the catalyst layer and the membrane layer, alleviate the "micro gap" between the membrane electrode (MEA), reduce the mass transfer resistance, and enhance the performance of water electrolysis single cells.
[0043] The organic-inorganic composite anion exchange membrane prepared by this invention has the following advantages: (1) The use of ultraviolet light curing for free radical cross-linking greatly shortens the film formation time, effectively inhibits membrane swelling, and improves mechanical strength; (2) The addition of highly hydrophilic nano-zirconia enables the cross-linked anion exchange membrane to maintain appropriate water absorption while reducing swelling, promotes ion conduction, and solves the problem of cross-linking reducing ion conductivity; (3) The membrane surface is coated with highly alkali-resistant zirconia to form a "protective layer" and improve service life; (4) Polar zirconia increases the bonding force between the catalyst layer and the membrane layer, alleviates the "micro-gap" between the membrane electrode, reduces mass transfer resistance, and enhances the performance of water electrolysis single cells; In summary, this invention utilizes a combination of cross-linking strategy and composite hydrophilic and highly alkali-resistant inorganic strategy (i.e., organic-inorganic composite) to comprehensively improve the performance of anion exchange membrane water electrolysis (AEMWE), and has a good application prospect in the field of anion exchange membrane water electrolysis (AEMWE).
[0044] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, but this does not imply any limitation on the scope of protection of the present invention. Attached Figure Description
[0045] Figure 1 This is a schematic flowchart of the preparation method of the composite anion exchange membrane of the present invention.
[0046] Figure 2 This is a graph showing the relationship between the conductivity and temperature of the products from Examples 1 to 4 of this invention. Detailed Implementation
[0047] To further understand the present invention, the preparation method provided by the present invention will be described in detail below through specific embodiments. The scope of protection of the present invention is not limited to the following embodiments, and the raw materials involved in the embodiments are all commercially available.
[0048] Example 1: Synthesis of poly(biphenylpiperidine thiol) crosslinked composite anion exchange membrane (PBP-SH)
[0049] (1) Preparation of polybenzylpiperidine (PBP)
[0050] Pour 1g of biphenyl into a dry 100ml round-bottom flask equipped with a magnetic stir bar, add 2-3ml of dichloromethane, and after complete dissolution, add 0.882ml of N-methyl-4-piperidinone under ice bath conditions, and slowly add 0.482ml of trifluoroacetic acid and 5.74ml of trifluoromethanesulfonic acid as catalysts. The polymerization reaction is carried out at 0℃ with magnetic stirring for 4 hours. It is important to note that the trifluoromethanesulfonic acid should be added slowly to ensure that there is no excessive fuming. During the reaction, the solution color can be observed to change from dark green to blackish purple. After the reaction is completed, precipitate the obtained polybiphenylpiperidine (PBP) in NaOH solution and wash it with deionized water 3-5 times until neutral. Finally, filter the product obtained during the precipitation process under reduced pressure and wash it with deionized water until neutral. Dry the obtained polybiphenylpiperidine (PBP) in an oven at 60℃ for later use.
[0051] (2) Preparation of poly(biphenylpiperidine-propylene) (PBP-Br)
[0052] Add 0.3g of poly(biphenylpiperidine) (PBP) prepared in step (1) to a dry round-bottom flask equipped with a magnetic flask, add 4ml of N-methylpyrrolidone, and after the poly(biphenylpiperidine) (PBP) dissolves, add 2.00g of 3-bromopropene, and react at 80℃ for 48h. After the reaction is complete, slowly pour the dark brown solution in the flask into ethyl acetate solution to precipitate, filter the product, and wash it three times with deionized water to obtain poly(biphenylpiperidine)-propene (PBP-Br).
[0053] (3) Preparation of quaternized polybis(piperidine)-propylene (PBP-Br-C)
[0054] Take 0.3g of poly(biphenylpiperidine-propylene) (PBP-Br) prepared in step (2), add it to a dry round-bottom flask equipped with a magnetic flask, add 5ml of dimethyl sulfoxide, and after it is completely dissolved, add 1.5mL of iodomethane. React at room temperature in the dark for 48h. After the reaction is complete, slowly pour the dark brown solution in the flask into ethyl acetate solution to precipitate. Filter the product and wash it three times with deionized water to obtain quaternized poly(biphenylpiperidine-propylene) (PBP-Br-C).
[0055] (4) Preparation of poly(piperidine thiol) crosslinked membrane (PBP-SH)
[0056] Take 0.3g of the quaternized polybis(piperidine)propene (PBP-Br-C) prepared in step (3), dissolve it in 7ml of dimethyl sulfoxide, add 0.02g of photoinitiator 2,2-dimethoxy-2-2-phenylethyl ketone and 90μL of 1,8-octanedithiol, and cast it into a film under ultraviolet light.
[0057] Example 2: Preparation of Zirconia-Polydiphenylpiperidinethiol Crosslinked Composite Anion Exchange Membrane (PBP-SH-Zr1)
[0058] (1) Preparation of polybenzylpiperidine (PBP)
[0059] Same as Example 1;
[0060] (2) Preparation of poly(piperidine-propylene) (PBP-Br)
[0061] Same as Example 1;
[0062] (3) Preparation of quaternized polybis(piperidine)-propylene (PBP-Br-C)
[0063] Same as Example 1;
[0064] (4) Preparation of poly(piperidine thiol) crosslinked membrane (PBP-SH)
[0065] Same as Example 1;
[0066] (5) Preparation of poly(piperidine thiol)-zirconia composite membrane (PBP-SH-Zr1)
[0067] 53.3 mg of zirconium dioxide (average particle size 200 nm) was dispersed in 53.3 mL of ethanol, mixed in 312 μL of polycarbazole ionomer, and sonicated for 5-6 hours to obtain a concentration of 1 mg / cm³. 2 The zirconium dioxide ionomer solution was uniformly coated on the surface of the membrane prepared in step (4) by ultrasonic spraying at 60°C. Then, the membrane was immersed in 1M NaOH solution for 24 hours and repeatedly rinsed with deionized water to obtain a hydroxyl-form membrane.
[0068] Example 3: Preparation of Zirconia-Polydiphenylpiperidinethiol Crosslinked Composite Anion Exchange Membrane (PBP-SH-Zr2)
[0069] (1) Preparation of polybenzylpiperidine (PBP)
[0070] Same as Example 1;
[0071] (2) Preparation of poly(piperidine-propylene) (PBP-Br)
[0072] Same as Example 1;
[0073] (3) Preparation of quaternized polybis(piperidine)-propylene (PBP-Br-C)
[0074] Same as Example 1;
[0075] (4) Preparation of poly(piperidine thiol) crosslinked membrane (PBP-SH)
[0076] Same as Example 1;
[0077] (5) Preparation of poly(biphenylpiperidine thiol)-zirconia composite membrane (PBP-SH-Zr2)
[0078] 106.6 mg of zirconium dioxide (average particle size 200 nm) was dispersed in 53.3 mL of ethanol, mixed in 624 μL of polycarbazole ionomer, and sonicated for 5-6 hours to obtain a concentration of 2 mg / cm³. 2 Zirconia ionomer solution; at 60°C, ultrasonic spraying is used to uniformly coat the surface of the membrane prepared in step (4). Then, the membrane is immersed in 1M NaOH solution for 24 hours and repeatedly rinsed with deionized water to obtain a hydroxyl-form membrane.
[0079] Example 4: Synthesis of zirconium dioxide-polybisphenylpiperidine thiol crosslinked composite anion exchange membrane (PBP-SH-Zr4).
[0080] (1) Preparation of polybenzylpiperidine (PBP)
[0081] Same as Example 1;
[0082] (2) Preparation of poly(piperidine-propylene) (PBP-Br)
[0083] Same as Example 1;
[0084] (3) Preparation of quaternized polybis(piperidine)-propylene (PBP-Br-C)
[0085] Same as Example 1;
[0086] (4) Preparation of poly(piperidine thiol) crosslinked membrane (PBP-SH)
[0087] Same as Example 1;
[0088] (5) Preparation of poly(piperidine thiol)-zirconia composite membrane (PBP-SH-Zr4)
[0089] 213.3 mg of zirconium dioxide (average particle size 200 nm) was dispersed in 53.3 mL of ethanol, mixed in 1248 μL of polycarbazole ionomer, and sonicated for 5-6 hours to obtain a concentration of 4 mg / cm³.2 Zirconia ionomer solution; at 60°C, ultrasonic spraying is used to uniformly coat the surface of the membrane prepared in step (4). Then, the membrane is immersed in 1M NaOH solution for 24 hours and repeatedly rinsed with deionized water to obtain a hydroxyl-form membrane.
[0090] like Figure 1 The diagram shows a flow chart of the preparation method for the composite anion exchange membrane; as shown. Figure 2 The figure shown is a graph showing the relationship between the conductivity and temperature of the products of Examples 1 to 4 of the present invention.
[0091] The conductivity of the prepared anion exchange membrane was measured using AC impedance spectroscopy on a standard electrochemical workstation, with a scanning frequency range of 10⁻¹⁰. 5 The ion conductivity-temperature variation graph was obtained by measuring the Hz. Tests showed that at 80℃, the conductivity of the membrane in Example 1 reached 100.5 mS / cm; the conductivity of the membrane in Example 2 reached 124.2 mS / cm; the conductivity of the membrane in Example 3 reached 138.3 mS / cm; and the conductivity of the membrane in Example 4 reached 167.7 mS / cm. These results meet the conductivity requirements for anion exchange membranes in water electrolysis.
[0092] Based on the above method, the composite membrane prepared by combining novel free radical crosslinking with coating of highly alkali-resistant and hydrophilic polar nano-inorganic materials maintains both good dimensional stability and high ionic conductivity. This is attributed to the crosslinked network structure promoting microphase separation and reducing swelling, while the hydrophilic zirconium dioxide coating further promotes OH- - The transport of OH; in addition, due to the coating of highly hydrophilic polar zirconium dioxide, an effective water management is formed in the catalyst layer, accelerating the OH transport. - Transport between the MEA interface (liquid-solid-solid) alleviates the micro-gap between the catalyst layer and the membrane, greatly reduces the interfacial resistance and charge transfer resistance, improves the performance of water electrolysis single cells, and has broad application prospects in anion exchange membrane water electrolysis cells.
[0093] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention, but do not limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A composite anion exchange membrane, comprising an inorganic material and a cross-linked anion exchange membrane, wherein the inorganic material is coated on the cross-linked anion exchange membrane, wherein... The structure of the backbone of a cross-linked anion exchange membrane is shown in general formula (I): ; Wherein: the main chain of the cross-linked anion exchange membrane is prepared by the condensation reaction of biphenyl monomers and ketone monomer N-methylpiperidinone; In the formula: n = 2 - 8; x=50, the corresponding anion is OH-. − ; Ar represents biphenyl, terphenyl, and bibenzyl; The inorganic substance is zirconium dioxide.
2. The composite anion exchange membrane according to claim 1, characterized in that: The inorganic material is nano-zirconia.
3. The method for preparing the composite anion exchange membrane according to any one of claims 1-2, comprising the following steps: (1) Dissolve biphenyl monomers in a solvent, add N-methylpiperidone monomers in the reaction molar ratio, continue to add trifluoroacetic acid and trifluoromethanesulfonic acid, ice bath, stir, after the reaction is completed, pour the product into sodium hydroxide solution, stir, remove excess acid, wash with deionized water until neutral, dry for later use, and obtain polybiphenylpiperidin polymer; (2) Dissolve the polybiphenylpiperidine polymer obtained in step (1) in a solvent, add 3-bromopropylene and potassium carbonate, heat and stir. After the reaction is complete, wash the product in a washing solvent, precipitate, and wash with deionized water to obtain polybiphenylpiperidine polyelectrolytes. (3) Dissolve the polybiphenylpiperidine polyelectrolyte obtained in step (2) in a solvent, add iodomethane, stir at room temperature in the dark, and after the reaction is complete, wash the product in a washing solvent, precipitate, and wash with deionized water to obtain quaternized polybiphenylpiperidine polyelectrolyte. (4) Dissolve the quaternized polybiphenylpiperidine polyelectrolyte prepared in step (3) in a solvent, add photoinitiator 2,2-dimethoxy-2-2-phenylethyl ketone and 1,8-octanedithiol, and carry out ultraviolet light reaction to obtain a homogeneous solution. (5) Cast the homogenized liquid obtained in step (4) into a film, coat it with an inorganic material, and obtain a coated film; (6) Immerse the coated membrane obtained in step (5) in sodium hydroxide or potassium hydroxide solution to obtain a hydroxide-type alkaline membrane.
4. The method for preparing the composite anion exchange membrane according to claim 3, characterized in that: In step (1), the solvent is dichloromethane or trichloromethane; the concentration of the sodium hydroxide solution is 3-5M; and the biphenyl monomer in step (1) is biphenyl or terphenyl.
5. The method for preparing the composite anion exchange membrane according to claim 4, characterized in that: In steps (2) and (4), the solvent is dimethyl sulfoxide, N-methylpyrrolidone, n-hexane, acetonitrile, cyclohexane or N,N-dimethylformamide; in step (3), the solvent is dimethyl sulfoxide or N-methylpyrrolidone; in steps (2) and (3), the washing solvent is cyclohexane, acetonitrile, ethyl acetate or tert-butyl methyl ether.
6. The method for preparing the composite anion exchange membrane according to claim 5, characterized in that: In step (1), the molar ratio of biphenyl monomers to N-methylpiperidone monomers is 1:1-1:1.5; in step (2), the molar ratio of polybiphenylpiperidine polymer to 3-bromopropylene is 1:0.5; the reaction temperature is 80℃ and the reaction time is 24-48 hours; in step (3), the molar ratio of polybiphenylpiperidine polyelectrolyte to iodomethane is 1:1.3; the reaction time is 24-72 hours; in step (4), the molar ratio of quaternized polybiphenylpiperidine polyelectrolyte to 2,2-dimethoxy-2-2-phenylethyl ketone is 1:0.1, and the molar ratio of quaternized polybiphenylpiperidine polyelectrolyte to 1,8-octanedithiol is 1:0.5; the reaction time under ultraviolet light is 0.5-2 hours.
7. The method for preparing the composite anion exchange membrane according to claim 6, characterized in that: In step (5), the inorganic material is a strongly hydrophilic and alkali-resistant polar nano-inorganic material; the polar nano-inorganic material is nano-zirconia; the amount of nano-inorganic material coated is 1 mg / cm³. 2 2mg / cm 2 4mg / cm 2 In step (6), the concentration of sodium hydroxide or potassium hydroxide solution is 0.1-3 mol / L, and the soaking time is 24-48 h.
Citation Information
Patent Citations
Physical crosslinking type polymer anion exchange membrane and preparation method thereof
CN114539578A
KR20210071810A